2018
DOI: 10.18502/ijaai.v17i5.307
|View full text |Cite
|
Sign up to set email alerts
|

Increased Total Serum Immunoglobulin E in Children Developing Mycoplasma pneumoniae-related Extra-pulmonary Diseases

Abstract: Mycoplasma pneumoniae has been recognized to be involved in several extra-pulmonary diseases, but the underlying immunologic mechanisms are still largely unknown. Recently, we observed a significant elevation of serum Immunoglobulin E (IgE) in a small group of these children. Here, we assessed total serum IgE levels in children affected with Mycoplasma pneumoniae-related extra-pulmonary diseases. We prospectively collected the data of 162 children admitted to the hospital (because of respiratory infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 29 publications
2
30
3
Order By: Relevance
“…In addition, we found that the rate of atopy was higher in the patients with extrapulmonary manifestations than in those without extrapulmonary manifestations. Interestingly, the serum total IgE levels were also higher in the extrapulmonary group than in the pulmonary group, which was consistent with the findings in the recent reports . The increased IgE levels can be considered a marker of immune dysregulation .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, we found that the rate of atopy was higher in the patients with extrapulmonary manifestations than in those without extrapulmonary manifestations. Interestingly, the serum total IgE levels were also higher in the extrapulmonary group than in the pulmonary group, which was consistent with the findings in the recent reports . The increased IgE levels can be considered a marker of immune dysregulation .…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the serum total IgE levels were also higher in the extrapulmonary group than in the pulmonary group, which was consistent with the findings in the recent reports. 7,8 The increased IgE levels can be considered a marker of immune dysregulation. 19,20 These findings may partly explain the relationship between atopy and extrarespiratory manifestations and indicate that an individual with an atopic predisposition could have an additional stimulation driving IgE production during MP infection;…”
Section: Ta B L E 2 Comparison Of Respiratory Severity Between Atopicmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have studied the immunologic response in respiratory infections caused by Mycoplasma pneumoniae (M. pneumoniae), which is an extracellular pathogen [10]. Increased total serum IgE levels were higher in hospitalized children diagnosed with different M. pneumoniae-related extra-pulmonary diseases compared with children that developed only classical respiratory illness due to M. pneumoniae [10]. The authors concluded that IgE probably had no role in the pathogenesis of these clinical manifestations, but the immune imprinting to produce IgE (i.e.…”
Section: Introductionmentioning
confidence: 99%